2016
DOI: 10.1111/jwas.12253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Density at Harvest on the Growth Performance and Profitability of Hatchery‐reared Spotted Rose Snapper, Lutjanus guttatus, Cultured in Floating Net Cages

Abstract: This study evaluated the effect of the density at harvest on the performance and profitability of hatchery‐reared spotted rose snapper cultured in cages. The fish were stocked at harvest densities of 15, 20, and 22 kg/m3 in cages of 222 and 286 m3. More than 39,000 snapper fingerlings with an initial weight of 14 g were stocked. The fish were fed an extruded diet and cultured over a 360 d period. The thermal growth coefficient ranged from 0.04 to 0.05 and survival was 95% for all treatments, with the highest f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
12
0
3
Order By: Relevance
“…In Mexico, L. guttatus is one of the most economically important fi sh species, which has caused its exploitation above optimum levels (Amezcua et al, 2006). In addition, this fi sh is considered as one of the best candidates for commercial aquaculture in the region (Alvarez-Lajonchère et al, 2012;Hernández et al, 2016). As far as we are aware 16 species of helminths (Anisakis sp., Hamacredium lariosi, Helicometrina nimia, Lecithochirium microstomum, Maculifer japonicus, Microcotyloides incisa, Neobivagina aniversaria, Polycryptocylis leonilae, Polymicrocotyle manteri, Pseudoterranova sp., Siphodera vinaledwardesii, Euryhaliotrema mehen, E. perezponcei, Haliotrematoides guttati, H. plectridium and H. spinatus) are known from L. guttatus Pérez-Ponce de León et al, 1999;García-Vargas et al, 2008;Soler-Jímenez & Fajer-Ávila, 2012;Soler-Jímenez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, L. guttatus is one of the most economically important fi sh species, which has caused its exploitation above optimum levels (Amezcua et al, 2006). In addition, this fi sh is considered as one of the best candidates for commercial aquaculture in the region (Alvarez-Lajonchère et al, 2012;Hernández et al, 2016). As far as we are aware 16 species of helminths (Anisakis sp., Hamacredium lariosi, Helicometrina nimia, Lecithochirium microstomum, Maculifer japonicus, Microcotyloides incisa, Neobivagina aniversaria, Polycryptocylis leonilae, Polymicrocotyle manteri, Pseudoterranova sp., Siphodera vinaledwardesii, Euryhaliotrema mehen, E. perezponcei, Haliotrematoides guttati, H. plectridium and H. spinatus) are known from L. guttatus Pérez-Ponce de León et al, 1999;García-Vargas et al, 2008;Soler-Jímenez & Fajer-Ávila, 2012;Soler-Jímenez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In general, it was observed that when feed was provided for tilapia and snapper in a mix-culture system, competition for food was apparently negligible coinciding with Simão et al (2013), who found that shrimp and tilapia FCR reared in tanks was not affected in mix-culture, even at high density, and with high tilapia ratio (Yuan et al, 2010). ) by Hernández et al (2015) and Hernández et al (2016), respectively, but similar to the reported by Alcala-Carrillo et al (2016) in close recirculating system (mean 1.3% d -1…”
Section: Discussionmentioning
confidence: 99%
“…Thus, fewer inputs/resources will need to be used per ton of production, and costs per ton of product will decrease. Recent examples of efficiency‐enhancing aquaculture technologies published in JWAS include: Hernández et al (), Huang et al (), and Kumar et al ().…”
mentioning
confidence: 99%